Spiritual and Aesthetic Education of Students and Youth through National Cultural Heritage (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The spiritual and aesthetic education of students and youth is a vital aspect of modern educational systems, aiming to foster well-rounded individuals who contribute meaningfully to society. This article explores how national cultural heritage can be utilized as an effective tool for promoting spiritual and aesthetic values in youth. Through a review of literature and theoretical analysis, the paper outlines the importance of integrating cultural heritage into education to shape students' ethical, emotional, and intellectual development. Additionally, the article delves into the role of various cultural elements – such as traditions, art, literature, music, and architecture – in influencing the aesthetic and spiritual growth of students. The research also discusses practical strategies for educators to incorporate these elements into teaching practices, ultimately cultivating a sense of identity, respect, and creativity among the younger generation.